Triple-negative accessory breast cancer occurring concurrently with primary invasive breast carcinoma: a case report - Chen, Ling; Wu, Zujian; Guo, Chi; Wan, Hengjin; Wu, Shouguo; Wang, Guoping (Frontiers in Surgery, 2024)
Introduction Accessory breast cancer (ABC) is an extremely rare condition, particularly the presence of triple-negative ABC with ipsilateral invasive in situ breast cancer. Binary breast tumors are controversial in terms of surgical methods and comprehensive treatment. Case presentation We share the case of a 64-year-old postmenopausal woman who presented with an underarm mass for 3 months. Ultrasonography and computed tomography suggested possible breast cancer with axillary lymph node metastasis. The patient underwent a left modified radical mastectomy combined with axillary lymph node dissection. The postoperative pathology confirmed a binary tumor, prompting us to initiate comprehensive treatment. Conclusion We present the treatment approach for a rare case of triple-negative para-breast cancer complicated with carcinoma in situ of the breast, hoping to contribute new therapeutic ideas for the treatment of this disease.